Congruência modular no ensino básico. - FERREIRA, Rosiane Barros (2018)
This text deals with modular arithmetic as a possible tool to be used since the initial grades of elementary education, from the sixth year. The theoretical basis is based on the elementary properties of congruence. This proposal is based on the fact that, from the initial stages, students have contact with concepts related to modular arithmetic. The formalization of these concepts would make possible a more concrete learning as well as the use of these concepts in the resolution of more varied problems from the initial years.